2018
DOI: 10.1111/jfd.12806
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of LPS, ß‐glucan and metabolic inhibitors on the respiratory burst and gene expression in Atlantic salmon macrophages

Abstract: Reactive oxygen species (ROS) production in macrophage-like cells is induced as an antimicrobial defence against invading pathogens. In this study, we have explored how different stimuli and metabolic inhibitors affect the level of respiratory burst in Atlantic salmon (Salmo salar L.) head kidney macrophage-like cells. Cells stimulated in vitro by bacterial lipopolysaccharide (LPS) and ß-glucan showed increased production of ROS compared to unstimulated cells. Both stimulation and costimulation by curdlan (ß-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Kidney macrophage burst activity was measured following a method from Ulvestad et al (2018) with a slight modification. Briefly, the head kidney was aseptically removed.…”
Section: Respiratory Burst Activity Assaymentioning
confidence: 99%
“…Kidney macrophage burst activity was measured following a method from Ulvestad et al (2018) with a slight modification. Briefly, the head kidney was aseptically removed.…”
Section: Respiratory Burst Activity Assaymentioning
confidence: 99%
“…As immunostimulants, â-glucans bind to macrophages and other white blood cells, improving the immunological responses of the host such as phagocytosis, lysozyme activity, respiratory burst, and cytokine release (Angulo et al 2017). Ulvestad et al (2018) reported that the head kidney macrophage-like cells of Atlantic salmon (Salmo salar L.) stimulated in vitro with bacterial lipopolysaccharide (LPS) and â-glucans showed increased production of reactive oxygen species (ROS) compared to unstimulated cells. Respiratory burst and associated ROS production also constitute important indicators of fish health status (Vera-Jimenez et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory burst and associated ROS production also constitute important indicators of fish health status (Vera-Jimenez et al 2013). Although â-glucans are not sources of ROS, they can stimulate ROS production via different mechanisms (Thitamadee et al 2014, Ulvestad et al 2018, Sánchez-Salgado et al 2019. ROS can elicit adverse effects in aquatic organisms and induce oxidative damage to lipids, proteins, and nucleic acids (Livingstone 2001, Valavanidis et al 2006.…”
Section: Introductionmentioning
confidence: 99%